Diretrizes para elaboração de uma política de indexação para acervos de centros de documentação e memória do teatro - Tiago Furtado Carneiro (2022)
Indexing policies are management tools and collaborate for the development of collections. They guide the entire process of organizing information, in terms of establishing guidelines for indexing and cataloging collections. This process contributes to improve the search, access and retrieval of information, promoting greater interaction between collections and their users. Within the scope of theater documentation and memory centers, there are studies on memory and theatrical heritage that promote discussions about the preservation of theatrical heritage as an intangible practice, and its documents and registration items. However, research on indexing policies for the theatrical context is still incipient. In light of this issue, this study has the general objective of raising a set of guidelines to support the elaboration of an indexing policy for the treatment of collections from theater documentation and memory centers, which include archival, bibliographic and museological informational resources, having based on the specificities observed in the Theater Research and Memory Center (in Portuguese, Centro de Pesquisa e Memória do Teatro or CPMT). The CPMT is a sector in the Galpão Cine Horto cultural center of the Grupo Galpão in Belo Horizonte, Minas Gerais, which gathers archival, bibliographic and museological collections specializing in theatrical memory. The methodology uses the methods of deductive approach and monographic procedure, with a qualitative approach of data analysis. In order to meet the objectives proposed in this study, the methodological procedures comprise eight stages: 1) Preparation, with the identification of the theme and selection of the research question; 2) Establishment of inclusion and exclusion criteria; 3) Integrative review: determination of sources and keywords; 4) Integrative review: identification of pre-selected and selected studies; 5) Narrative review: identification and selection of studies; 6) Categorization of selected studies; 7) Mapping of guidelines based on activities carried out at the CPMT and 8) Interpretation of results. The results show a set of guidelines that must be observed when designing an indexing policy for theater document and memory centers and show hybrid guidelines, as they involve general issues and also specificities related to archival science, library science and museology. Guided by the needs identified in CPMT, it was already possible to visualize some guidelines that are necessary for the construction of indexing policies that act in spaces responsible for theatrical collections. Looking ahead, it is concluded that it is essential to formalize procedures, produce documents and manuals for indexing policies that serve as guidelines for current services and as concrete proof of the evolution of the activities of theater documentation and memory institutions.